1988
DOI: 10.1007/bf00603948
|View full text |Cite
|
Sign up to set email alerts
|

Daily hoarding opportunity entrains the pacemaker for hamster activity rhythms

Abstract: The effects on activity rhythms of a daily 30 min opportunity to leave the home cage and hoard seeds from an open field were assessed in Syrian hamsters housed in continuous dim illumination. Six of ten hamsters responded with clear entrainment of their activity rhythms to the hoarding opportunity, as demonstrated by responses to phase shifts and by the onset phase of subsequent freerunning rhythms. No entrainable component separate from the freerunning rhythm was ever observed. Two hamsters showed phase shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Feeding a rat at restricted intervals each day makes it possible to entrain some activity rhythms leaving others to free-run (Boulos & Terman, 1980;Coleman et al, 1982). However, in hamsters a periodic opportunity to hoard (Rusak et al, 1988) or periodic arousal through social interaction or cage changing (Mrosovsky, 1988) entrains all components of rhyhtmic activity. Taken together the effects of melatonin on its circadian timing system, its role as an additional non-photic zeitgeber cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding a rat at restricted intervals each day makes it possible to entrain some activity rhythms leaving others to free-run (Boulos & Terman, 1980;Coleman et al, 1982). However, in hamsters a periodic opportunity to hoard (Rusak et al, 1988) or periodic arousal through social interaction or cage changing (Mrosovsky, 1988) entrains all components of rhyhtmic activity. Taken together the effects of melatonin on its circadian timing system, its role as an additional non-photic zeitgeber cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Moore & Eichler (1972), and Stephan & Zucker (1972), demonstrated that lesions in the suprachiasmatic nuclei abolished the circadian rhythm of drinking, locomotor activity, and corticosterone rhythm in rats (Moore & Eichler 1972); however, in rats with hypothalamic lesions placed on schedules of restricted feeding, pre-feeding activity was still evident (Phillips & Mikulka 1979, Stephan et al 1979a, b, Moore 1980, Stephan 1981. In contrast, according to Rusak et al (1988) ablations of the suprachiasmatic nuclei in hamsters did not unmask any other oscillator system. As far as we know, hypothalamic ablation, designed to investigate circadian rhythms in behaviour or physiology, has never been undertaken in fish species, but it has been performed on a cyclostome, Eptutretus burgeri.…”
Section: Speciesmentioning
confidence: 96%
“…Animals that run little after an arousing stimulus may fail to shift because they do not stay awake, whereas the occasional animal that shifts despite little running may do so because it does remain awake. This latter possibility, and potential contributions of nonspecific arousal to shifts induced by nonphotic stimuli, was noted in some of the earliest work on phase resetting by behavioral manipulations (Mrosovsky, 1988;Rusak et al, 1988;Honrado and Mrosovsky, 1989;Turek, 1989). More recently, it has been reported that brief episodes of arousal, induced by a single intraperitoneal injection of saline, can induce phase advance shifts without substantial locomotor activity, although these shifts are much smaller (ϳ60 min) and exhibit a more constrained circadian phase dependence than those induced by exercise procedures (Mead et al, 1992;Hastings et al, 1998).…”
mentioning
confidence: 92%